Equivalence of utilitarian maximal and weakly maximal programs - Kuntal Banerjee; Tapan Mitra (Cornell University, Center for Analytical Economics (CAE), 2009)
For a class of aggregative optimal growth models, which allow for a non-convex and non-differentiable production technology, this paper examines whether the set of utilitarian maximal programs coincides with the set of weakly maximal programs. It identifies a condition, called the Phelps-Koopmans condition, under which the equivalence result holds. An example is provided to demonstrate that the equivalence result is invalid when the Phelps-Koopmans condition does not hold.
Keywords: C61; D90; E10; O41; 330; Utilitarian Maximal; Weakly Maximal; Phelps-Koopmans condition; Aggregative growth models